From Zero to Sixty: Establishing Research Data Services from Scratch - Briney, Kristin (My University, 2015)
What does it take to create research data services where none existed before? Kristin Briney will discuss establishing Data Services at the University of Wisconsin-Milwaukee. Her talk will include strategy and lessons learned 18 months into the process.